The effects of glutaraldehyde on the control of single and dual biofilms of Bacillus cereus and Pseudomonas fluorescens - Simões, Lúcia C. (2011)
Glutaraldehyde (GLUT) was evaluated for control of single and dual species biofilms of Bacillus cereus and Pseudomonas fluorescens on stainless steel surfaces using a chemostat system. The biofilms were characterized in terms of mass, cell density, total and matrix proteins and polysaccharides. The control action of GLUT was assessed in terms of inactivation and removal of biofilm. Post-biocide action was characterized 3, 7, 12, 24, 48 and 72 h after treatment. Tests with planktonic cells were also performed for comparison. The results demonstrated that in dual species biofilms the metabolic activity, cell density and the content of matrix proteins were higher than those of either single species. Planktonic B. cereus was more susceptible to GLUT than P. fluorescens. The biocide susceptibility of dual species planktonic cultures was an average of each single species. Planktonic cells were more susceptible to GLUT than their biofilm counterparts. Biofilm inactivation was similar for both of the single biofilms while dual biofilms were more resistant than single species biofilms. GLUT at 200 mg l71 caused low biofilm removal (510%). Analysis of the post-biocide treatment data revealed the ability of biofilms to recover their activity over time. However, 12 h after biocide application, sloughing events were detected for both single and dual species biofilms, but were more marked for those formed by P. fluorescens (removal 440% of the total biofilm). The overall results suggest that GLUT exerts significant antimicrobial activity against planktonic bacteria and a partial and reversible activity against B. cereus and P. fluorescens single and dual species biofilms. The biocide had low antifouling effects when analysed immediately after treatment. However, GLUT had significant long-term effects on biofilm removal, inducing significant sloughing events (recovery in terms of mass 72 h after treatment for single biofilms and 42 h later for dual biofilms). In general, dual species biofilms demonstrated higher resistance and resilience to GLUT exposure than either of the single species biofilms. P. fluorescens biofilms were more susceptible to the biocide than B. cereus biofilms.